The impact of lifetime interpersonal and intentional trauma on cognition and vulnerability to psychosis in bipolar disorder. Issue 5 (9th September 2021) - Lebovitz, Julia G.; Millett, Caitlin E.; Shanahan, Meg; Levy-Carrick, Nomi C.; Burdick, Katherine E.
Abstract : Background: Studies have shown that over half of individuals with bipolar disorder experience early-life trauma, which may influence clinical outcomes, including suicidality and presence of psychotic features. However, studies report inconsistent findings regarding the effect of trauma on cognitive outcomes in bipolar disorder. Aims: Our study explores the effect of lifetime trauma on the level of vulnerability to psychosis and cognitive performance in participants with bipolar disorder. Method: We evaluated lifetime trauma history in 236 participants with a diagnosis of bipolar disorder type 1 or 2, using the Structured Clinical Interview for DSM-IV and the Childhood Trauma Questionnaire. We classified trauma types based on the Substance Abuse and Mental Health Services Administration's concept of trauma, which characterises the type of experienced trauma (e.g. interpersonal and intentional, accidental or naturally occurring). Our primary outcome measures of interest were vulnerability to psychosis (Schizotypal Personality Questionnaire), cognitive performance (MATRICS Consensus Cognitive Battery) and social functioning (Social Adjustment Scale Self-Report). Results: Multivariate analysis of covariance showed a significant effect of trauma type on the Schizotypal Personality Questionnaire cognitive–perceptual domain (F(3) = 6.7, P < 0.001). The no-trauma group had lower cognitive–perceptual schizotypal features compared with the accidental and intentional trauma ( P < 0.001) and interpersonal and intentional trauma ( P = 0.01) groups. Conclusions: Our results highlight the need for careful trauma inquiry in patients with bipolar disorder, and consideration of how trauma-focused or -informed treatments may be an integral part of treatment planning to improve outcomes in bipolar disorder.